A REVIEW OF THE MODERN TRENDS IN THE SURGICAL TREATMENT OF MALIGNANT BONE TUMORS IN CHILDHOOD - Kircho Patrikov (Journal of the Bulgarian Orthopaedics and Trauma Association)
Osteogenic sarcoma is a primary bone tumor characterized by malignant cells producing osteoid matrix. Ewing's sarcoma is a rare highly malignant bone tumor and second in frequency after osteosarcoma in children. Current treatment of both entities is multidisciplinary and consists of preoperative chemotherapy (sometimes in combination with radiation therapy), surgery to remove the tumor, and postoperative chemotherapy. Surgical treatment takes the main place for local control with excision of the tumor from the affected limb, rotational plasty and limb salvage operations with subsequent reconstructions.Limb salvage surgeries allow limb preservation and functionality, and with long-term follow-up the survival rate could reach 90% in the first 10 years.